Exploring the fungal community structure and assembly in different tissues of Gymnadenia conopsea - Yin, Xiu; Lu, Yazhou; Quan, Hong; Zhang, Erhao; Wang, Zhongbin (Frontiers in Microbiology, 2025)
Gymnadenia conopsea has high economic value and can be used as a medicinal and ornamental plant. Owing to its low natural reproduction rate and overexploitation, the risk of extinction of this plant is gradually increasing. Endophytic fungi play crucial roles in host growth and development; however, the characteristics of the endophytic fungal community in various tissues of G. conopsea have not been fully characterized. Illumina MiSeq high-throughput sequencing technology was employed to sequence the fungal ITS (A non-coding DNA sequence located between the 18S rRNA gene and the 5.8S rRNA gene within the ribosomal RNA gene cluster) region, thereby characterizing the community structure and assembly processes of endophytic fungi in roots, stems, leaves, and fruits. A total of 7,371 OTUs were obtained from all the samples and were dominated by Ascomycota and Basidiomycota. The richness indices of various tissues were significantly different, whereas the diversity indices were not significantly different. The composition of the dominant genera differed; overall, the compositions of the endophytic fungal communities were similar among the leaf, stem, and fruit tissues. The relative abundances of Ceratobasidium, Cadophora, and Mortierella were significantly higher in root tissues than in other tissues, G. conopsea roots should be prioritized as the material for isolating growth-promoting endophytic fungi. Cooccurrence network analysis revealed that endophytic fungi in different tissues presented typical modular structures and the network was mainly positive. The assembly processes in different tissues were affected mainly by deterministic factors. The proportions of pathotrophs, saprotrophs, and symbiotrophs were different among various tissues, and the proportion of pathotrophs was greater than those of saprotrophs and symbiotrophs. In conclusion, tissue type affects the composition of endophytic fungi. Furthermore, by dissecting the composition and functions of the fungal community associated with G. conopsea, this study aims to provide a reference for exploring the interaction mechanisms between endophytic fungi and G. conopsea.